Problems and Possibilities of Development for the Market of Securities in Developing Countries - NURASHEVA, Kulyanda; KULANOVA, Darikul; MERGENBAYEVA, Aziza; ABDIKERIMOVA, Gulzhanar (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2019)
The purpose of the study is to show the problems of the securities market and ways to improve it, using the example of Kazakhstan as a country with a developing economy. Weakness of institutions of development and instability of the banking sector hinder the development of the stock market. Real household income is slowly growing, inflation and depreciation of the national currency take place, this decreases the possibility to invest in securities. The risks of buying securities by the population are not calculated, there are no clear guarantees of common shareholders’ rights, and the payback raises big questions because of law imperfection. In order to substantiate the real possibilities and desire of people to spend money to purchase municipal bonds, the random sampling method was used to conduct a survey and interviewing of representatives of various social groups. The study has shown that citizens have the willingness to purchase securities. However, first, it is necessary to create an innovative economy, implement in the regions attractive projects in infrastructure, tourism, agricultural products processing, to form efficient clusters in the regions. Only the quasi-public sector is involved in the current scheme for issuing municipal bonds. The authors recommend involving the assets of pension funds, insurance companies, as well as incomings of the population: the most mass shareholder. The problems and proposals considered in the article are of interest to the post-Soviet countries that face the need to develop the stock market.